Lecturers overcoming challenges using teaching strategies and digital tools to implement blended learning at a private higher education institution in South Africa - Govender, T.; Verne, S. (South African Journal of Higher Education, 2026)
The Fourth Industrial Revolution has ushered in an era where technology significantly impacts various aspects of life, including higher education. Blended learning, which combines synchronous and asynchronous learning, has gained popularity as a pedagogical approach. However, its effective implementation is a challenge, particularly in the context of the COVID-19 pandemic and technological obstacles faced in South Africa. This study focused on lecturers’ pedagogical practices to implement blended learning. With a specific aim to understand teaching and learning strategies preferred by lecturers to integrate digital tools that facilitate the blended learning approach. Using heutagogy and constructivism as theoretical frameworks, the study aimed to uncover insights into the lecturer’s teaching and learning practices to overcome challenges in designing and facilitating blended learning modules. Through a qualitative analysis, the following themes emerged student engagement, pedagogical practices, digital tools, and feedback emerged, highlighting the complexities and opportunities in a blended learning classroom. The findings emphasize the importance of tailoring methods to students’ needs and subject matter, aligning with constructivist principles. Recommendations include promoting professional development opportunities, addressing infrastructure issues, and fostering a supportive learning environment.